A Review of Technological Pedagogical Content Knowledge - Chai, Ching Sing; Koh, Joyce Hwee Ling; Tsai, Chin-Chung (Educational Technology ＆ Society, 2013)
This paper reviews 74 journal papers that investigate ICT integration from the framework of technological pedagogical content knowledge (TPACK). The TPACK framework is an extension of the pedagogical content knowledge (Shulman, 1986). TPACK is the type of integrative and transformative knowledge teachers need for effective use of ICT in classrooms. As a framework for the design of teacher education programs, the TPACK framework addresses the problem arising from overemphasis on technological knowledge in many ICT courses that are conducted in isolation from teachers' subject matter learning and pedagogical training. The present review we have conducted indicates that TPACK is a burgeoning area of research with more application in the North American region. Studies conducted to date employed varied and sophisticated research methods and they have yielded positive results in enhancing teachers' capability to integrate ICT for instructional practice. However, there are still many potential gaps that the TPACK framework could be employed to facilitate deeper change in education. In particular, we suggest more development and research of technological environments base on TPACK; study of students' learning conception with technology; and cross fertilization of TPACK with other theoretical frameworks related to the study of technology integration.